2023
DOI: 10.3390/nu15153369
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Behaviour and Sociocultural Determinants of Dietary Diversity among Rural Women of Reproductive Age: A Case of Amhara Region, Ethiopia

Simegn Kassa Alamirew,
Stefanie Lemke,
Barbara Stadlmayr
et al.

Abstract: Women of reproductive age have specific nutritional requirements due to pregnancy and lactation. Little is known about the sociocultural determinants of dietary diversity among women of reproductive age. This study assesses trends of dietary behaviour and associated determinants of dietary diversity of women of reproductive age. A community-based cross-sectional study was conducted in the Amhara region of Ethiopia in 2019. Using multistage systematic random sampling, the dietary diversity of n = 421 women of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…For example, many of the Waala ethnic groups are Muslims, and consuming vegetables and fruits heightened during Ramadan, possibly contributing to high dietary diversity. The results are consistent with the study conducted by Alamirew et al in rural Ethiopia, which concluded that cultural beliefs and ethnic backgrounds play a significant role in shaping the dietary preferences of households [ 66 ]. Additionally, the Waala ethnic group dominates petty trading in the region.…”
Section: Discussionsupporting
confidence: 92%
“…For example, many of the Waala ethnic groups are Muslims, and consuming vegetables and fruits heightened during Ramadan, possibly contributing to high dietary diversity. The results are consistent with the study conducted by Alamirew et al in rural Ethiopia, which concluded that cultural beliefs and ethnic backgrounds play a significant role in shaping the dietary preferences of households [ 66 ]. Additionally, the Waala ethnic group dominates petty trading in the region.…”
Section: Discussionsupporting
confidence: 92%
“…Using one 24 h recall period provides an assessment of the diet at the population level and is useful for monitoring progress or performing interventions [25]. Moreover, compared with longer timeframes for recall, a 24 h period was chosen as it may be less subject to recall error and less cumbersome for a respondent, and also conforms to the recall time period used in many dietary diversity studies [23,[25][26][27]. Then, based off their answers to the questionnaire, we computed a Women's Dietary Diversity Score (WDDS) for each participant.…”
Section: Dietary Diversitymentioning
confidence: 99%